Examining The Relationship Between Compassion Fatigue and Caring Behaviors in Nurses: A Cross- Sectional Study - Zekiye Türkan Aslan; Seda Tuğba Baykara Mat (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: The study aimed to examine the relationship between compassion fatigue and caring behaviors in nurses. Method: The population of the cross-sectional design research consists of nurses serving in three hospitals affiliated with the Ministry of Health in Istanbul between 01.12.2022 and 01.12.2023 (N: 1,620). The study was conducted with 346 nurses who volunteered to participate in the research (n: 346). Personal and Professional Information, Compassion Fatigue-Brief Scale, and Caring Behaviors Scale-30 were used. Descriptive statistics, independent groups t test, one-way ANOVA tests and Pearson correlation analysis were used to analyze the data. Results: It was determined that 78.6% of the participants were women, the average age was 27.97 and the weekly working hours were 47.22. It was observed that 83.5% of the participants worked in shifts, 33.5% were dissatisfied with working in the institution and 13.0% were dissatisfied with working in the unit. The compassion fatigue scale score was found to be 60.62 (23.26), and the caring behaviors scale score was 159.37 (20.69). It was determined that female participants and those who were dissatisfied with their field of work had high compassion fatigue scores, and those who were satisfied had high care behavior scores (p<0.05). There was no statistically significant relationship between compassion fatigue and caring behaviors scale and subscale scores. It was observed that there was a positive significant relationship between weekly working hours and compassion fatigue and caring behaviors scale scores (p<0.05). Conclusion: It was revealed that nurses' compassion fatigue was at a moderate level, and women and those who were dissatisfied with the unit they worked in experienced high compassion fatigue. Weekly working hours were found to be effective on compassion fatigue and caring behaviors. It is recommended to improve working environments in order to improve the quality of care.